Effect of Protein-Energi Concentration in Feed on Body Weight Gain, Energy and Protein Efficiency in the Growth Period of Merawang Chicken - Sidadolog, JHP; Yuwanta, T (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
The study was conducted to investigate the effect of protein-energy concentration in feed on using of energy and proteinÂ efficiency in the growth performance of Merawang chicken, as breed local of native chicken. This study was using 101 day old chicks from mating groups of six sires and 20 dams. The chickens were identification individually based on its parent groups, respectively. All of the chickens were dividedÂ in three groups of feeding treatment that was different in protein-energy concentration but had the same of protein : energy ratio (1:150). The rations were namely (1) high concentration (21% protein and 2240 kcal/kg ME) for 36 chicks; (2) medium concentration (18% protein and 2670 kcal/kg ME) for 35 chicks and (3) low concentration (15% protein and 3140 kcal/kg ME) for 30 chicks, respectively. The weekly collected data were individually of body weight and feed consumption for 12 week of old.Â The data were statistically analyzed by one way classification of completely randomized design (CRD) forÂ body weight gain, feed consumption, feed conversion, protein and energy intake, and efficiency of using protein and energy for body weight gain. The mean different was tested by Duncanâs multiple range of test. The results showed that body weight gain was only significantly different (Pâ¥0.001) at 2nd and 3rd week of ages and then it was statistically no difference any more up to 12 weeks old of age. Weekly and cumulative feed consumption and feed conversion showed a highly significant different (Pâ¥0.001). A lower feed consumption and feed conversion were found in a high protein-energy concentration and the higher in a low protein-energy concentration treatment. The best efficiency energy and protein (Pâ¥0.001) was found in the treatment of medium and low protein-energy concentrations and the lowest one in the high protein-energy concentration. The conclusions was that the medium protein-energy concentration ration (protein 18% and 2690 kcal/kg ME) was the best ration for the first four weeks of age and then the low and the medium could be fed up to 12 weeks of age without different effect on body weight gain. The high protein-energy ration was not recommended, because of using protein and energy for body weight gain had a lower efficiency. (Animal Production 11(1): 15-22 (2009)Key Words : merawang chickens, body weight gain , energy and protein efficiency